Musculoskeletal injuries and training patterns in junior elite orienteering athletes - Roos, L.; Taube, W.; Zuest, P.; Clénin, G.; Wyss, T. (Canadian Respiratory Journal, 2015)
Findings about the relation between musculoskeletal injuries and training patterns in orienteering athletes are sparse. Therefore, the musculoskeletal injuries and training patterns of 31 Swiss elite orienteering athletes aged 18-19 years were analyzed in a retrospective study. Individual training diaries and medical records were used to assess training data and injury history, respectively. Group comparisons and a multiple linear regression (MLR) were performed for statistical analysis. The junior elite orienteering athletes performed 7.38 ± 2.00 training sessions weekly, with a total duration of 455.75 ± 98.22 minutes. An injury incidence rate (IIR) of 2.18 ± 2.13 injuries per 1000 hours of training was observed. The lower extremity was affected in 93% of all injuries, and the knee (33%) was the most commonly injured location. The MLR revealed that gender and six training variables explained 60% of the variance in the injury severity index in this study. Supported by the low IIR in the observed age group, the training protocol of the junior elite orienteering athletes was generally adequate. In comparison to elite track, marathon, and orienteering athletes, the junior elite athletes performed less high-intensity interval training (HIIT). However, more frequent HIIT seems to be a protective factor against injuries.